Spinel ceramic material, preparation method and dielectric property testing method
Through the improved spinel ceramic material preparation method, the problems of impurity of samples and poor dielectric properties were solved, and high-purity ceramic materials were prepared, with excellent dielectric properties, and are suitable for high-performance electrical devices in the modern electronic industry.
Patent Information
- Application Number
- CN202510409554.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-07-04
AI Technical Summary
In the prior art, ceramic materials have problems such as impure samples, poor dielectric performance, large dielectric loss and obvious leakage current effects, which are not conducive to application.
The sample was weighed at a molar ratio of 1:1:(4-x):2x by Li2CO3, In2O3, Cr2O3 and CuO powder, and then pre-fired, ball milling and drying, using anhydrous alcohol as the ball milling medium, pressed into a wafer, and then discharged at 550°C and then raised to 1000°C for sintering for 24 hours, and prepared spinel ceramic materials for dielectric performance testing.
The prepared ceramic materials have high purity, excellent dielectric properties, large dielectric constant and small dielectric loss. They are suitable for the manufacture of high-performance capacitors, dielectric resonators and filters, and improve circuit efficiency and stability.
Smart Images

Figure CN120247558A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic material preparation, and specifically to spinel ceramic materials, preparation methods and dielectric property testing methods. Background Art
[0002] In the prior art: Yoshihiko Okamoto, et al. Magnetic Phase Diagram of the Breathing Pyrochlore, Antiferromagnet LiGa 1-x In x Cr4O8, Journal of the Physical Society of Japan, 2015, 84:043707.
[0003] In 2015, the Okamoto group in Japan mixed two materials, LiGaCr4O8 and LiInCr4O8, in a molar ratio of 1 - x:x, calcined them at 1100 °C for three days and ground them several times in the middle to prepare LiGa 1-x In x Cr4O8 samples. It can be seen that there is a Cr2O3 impurity phase between 30 - 40 degrees. Figure 1
[0004] Dong - Yi Wang, et al. The Complex Magnetism in the Breathing Pyrochlore LiIn(Cr 1-x Rh x )4O8, CHIN.PHYS.LETT. 2016, 33(12):127501.
[0005] In 2016, the Shu Lei group at Fudan University used starting raw materials Li2CO3, In2O3 and Cr2O3 / Rh2O3. The raw materials were dried overnight at 120 °C and then weighed to a molar ratio of 1:1:4. Then the raw materials were mechanically processed and mixed, pressed into sheets and sintered at 1100 °C for 48 hours. The heated samples were crushed into powders, pressed into sheets again, and then sintered up to four times to ensure uniformity. The Figure 2 X - ray diffraction pattern obtained Figure 2 is the X - ray diffraction pattern of LiGa 1-x InxCr4O8, and there is an In2O3 impurity phase between 30 - 40 degrees.
[0006] Hui Liu,et al.The effect of manganese doping on the structural,magnetic and dielectric properties of breathing pyrochlore LiInCr 4-x Mn x O8,Journal of Alloys and Compounds,2021,891:162098。
[0007] In 2021, the raw materials Li2CO3, In2O3, and Cr2O3 / MnO2 were dried at 200 °C for 10 hours, then weighed according to a molar ratio of 1:1:4. The starting materials were mechanically mixed and pre-sintered at 800 °C without pressing for 12 hours to eliminate the carbonates therein. To avoid reactions with the containers, the grinding and sintering containers used were an agate mortar and a high-purity corundum crucible, respectively. After heating, the samples were pressed into sheets and sintered at 1000 °C for 24 hours, then sintered at 1150 °C for another 24 hours with an intermediate grinding, from Figure 3 It can be seen that there is a small In2O3 impurity phase at an angle of more than 30 degrees, which may be caused by the volatilization of Li2CO3.
[0008] All existing technologies use the solid-state reaction method to prepare ordinary polycrystalline samples of LiInCr4O8. Polycrystalline materials are composed of many single-crystal grains and grain boundaries surrounding the single-crystal grains. They are a collection of single crystals with many oriented grains. The grain boundaries in polycrystals can scatter electrons and phonons, resulting in a decrease in electrical conductivity and thermal conductivity. When the grain size in polycrystals is small, it is difficult for the grains to visually present images such as crystal planes and crystal edges. The sample clarity is poor, showing scattered light. Ordinary polycrystalline samples have poor hardness, are easy to break, and have poor applicability.
[0009] Ceramic materials are a class of inorganic non-metallic materials made through shaping and high-temperature sintering. They have excellent insulation, corrosion resistance, high temperature resistance, high hardness, low density, radiation resistance, etc. Due to some special properties of ceramics, they can also be used as functional materials and have good application performance.
[0010] The highest sintering temperature in the existing technology is 1050 to 1150 degrees. Since the melting point of lithium carbonate Li2CO3 is relatively low, only 618 degrees Celsius, the relatively high sintering temperature is likely to cause the volatilization of the raw material Li2CO3, resulting in the presence of In2O3 or Cr2O3 impurity phases in the prepared sample, making the sample impure. Since Li2CO3 is slightly soluble in water, if deionized water is used for ball milling during the preparation process, the phase formation will also be impure. For the polycrystalline samples prepared in the past, the dielectric properties are not good, the dielectric loss is relatively large, and the leakage current effect is significantly unfavorable for applications. Summary of the Invention
[0011] The purpose of the present invention is to provide a spinel ceramic material, a preparation method, and a dielectric property testing method to solve the problems of impure samples, poor dielectric properties, large dielectric losses, and obvious leakage current effects that are unfavorable for applications as mentioned in the above background technology.
[0012] To achieve the above purpose, the present invention aims to provide a preparation method for a spinel ceramic material, including the following steps:
[0013] S1. Take Li2CO3, In2O3, Cr2O3, and CuO powders and weigh the samples according to the molar ratio of 1:1:(4 - x):2x.
[0014]
[0015] S2. Place the weighed powders in a corundum crucible for pre-sintering;
[0016] S3. Pour the pre-sintered powders into a grinding jar, add zirconia balls and absolute ethanol, and ball mill for 2 hours;
[0017] S4. Pour the ball-milled powders into a flat ceramic dish and place it in an electrothermal blast drying oven for drying;
[0018] S5. Put the scraped powder material in an agate mortar, add 10% by mass of polyvinyl alcohol ceramic glue, and grind with a grinding rod to make the glue and the powder evenly mixed;
[0019] S6. Sieve the powder material after adding the glue through a 40-mesh stainless steel sieve;
[0020] S7. Press the sieved powder material into a round piece with a tablet press and place it in a corundum crucible;
[0021] S8. Place the corundum crucible containing the round piece in a muffle furnace, calcine at 550 °C for 4 hours to remove the binder, and then directly raise the temperature to 1000 °C and calcine for 24 hours to prepare the LiInCr 4-x Cu x O8 ceramic sample.
[0022] As a further improvement of the technical solution, the mesh number of the Li2CO3, In2O3, Cr2O3 and CuO powders in the step S1 is 200 mesh.
[0023] As a further improvement of the technical solution, the value of x in the step S1 is 0, 0.2, 0.4, 0.5.
[0024] As a further improvement of the technical solution, the conditions for pre-sintering in the step S2 are: pre-sintering at 900 °C for 4 hours.
[0025] As a further improvement of the technical solution, anhydrous alcohol is used as the ball milling medium in the step S3.
[0026] As a further improvement of the technical solution, the conditions for drying in the step S4 are: drying at a temperature of 85 °C for 4 hours.
[0027] As a further improvement of the technical solution, the diameter of the wafer in the step S7 is 13 mm and the thickness is 1 - 2 mm.
[0028] As a further improvement of the technical solution, the sintering temperature threshold in the step S8 is 1000 ± 20 °C and the sintering time threshold is 24 ± 2 hours.
[0029] The present invention also provides a method for testing the dielectric properties of the spinel ceramic material, including the following steps:
[0030] A1. Dielectric constant and loss test: Use an impedance analyzer to measure the dielectric constant and dielectric loss of the sample in the frequency range of 20 Hz - 30 MHz, and the test temperature range is from room temperature to 350 °C;
[0031] A2. Threshold determination: Set the dielectric property threshold, the dielectric constant ≥ 5000 (low frequency 20 Hz), the dielectric constant ≥ 7 (high frequency 30 MHz), the dielectric loss ≤ 0.02 (high frequency 30 MHz). If the sample meets the threshold, it is determined as a high-performance dielectric material.
[0032] The present invention also provides a spinel ceramic material, and the spinel ceramic material is prepared by the preparation method of the above spinel ceramic material.
[0033] Compared with the prior art, the beneficial effects of the present invention are:
[0034] 1. The LiInCr 4-x Cu x O8 ceramic material prepared by the present invention has excellent insulation, corrosion resistance, high temperature resistance, high hardness, low density, radiation resistance and other advantages, and is more compact, easier to form and more practical than polycrystalline materials.
[0035] 2. The ceramic materials prepared by the present invention have less sintering time and lower sintering temperature than polycrystalline materials. At the same time, ball milling with absolute alcohol reduces the volatilization of Li2CO3, and the prepared samples have fewer impurity phases and higher purity.
[0036] 3. The ceramic samples prepared in the present invention are pre-sintered at a constant temperature of 900 °C for 4 hours, and then sintered at 1000 °C for 24 hours to form a phase after adding glue. Conventional polycrystalline samples are sintered at 1050 - 1150 °C, and the constant temperature time is longer, mostly 48 hours or even several days. By comparison, the ceramic materials prepared by the present invention have lower sintering temperature and shorter sintering time, reducing the volatilization of raw material lithium carbonate Li2CO3. At the same time, absolute alcohol instead of deionized water is used in the ball milling process, making the prepared materials have higher purity.
[0037] 4. The ceramic samples prepared in the present invention have better dielectric properties than conventional polycrystalline samples. The ceramic dielectric materials prepared by the technology of the present invention have a larger frequency range (20 Hz - 30 MHz) in dielectric property testing, with a larger dielectric constant and smaller dielectric loss, and better dielectric properties. They can be used to manufacture high-performance capacitors, dielectric resonators, filters and other devices, improving the efficiency and stability of circuits, and having good application value in modern electronic industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is the X-ray diffraction pattern of LiGa 1-x In x Cr4O8 in the prior art, where the abscissa is the diffraction angle and the ordinate is the diffraction intensity.
[0039] Figure 2 is the X-ray diffraction pattern of LiIn(Cr 1-x Rh x )4O8 in the prior art, where the abscissa is the diffraction angle and the ordinate is the diffraction intensity.
[0040] Figure 3 is the X-ray diffraction pattern of LiInCr 4-x Mn x O8 in the prior art, where the abscissa is the diffraction angle and the ordinate is the diffraction intensity.
[0041] Figure 4 is the preparation flow chart of the present invention.
[0042] Figure 5 is the X-ray diffraction pattern of the LiInCr 4-x Cu x O8 ceramic sample of the present invention, where the abscissa is the diffraction angle and the ordinate is the diffraction intensity.
[0043] Figure 6For the LiInCr of the present invention 4-x Cu x Scanning electron microscope image of the LiInCr 4-x Cu x O8 ceramic sample, where the abscissa is the particle size and the ordinate is the number of grains with different particle sizes.
[0044] Figure 7 For the LiInCr of the present invention 4-x Cu x Temperature-spectrum curve of the dielectric constant of the LiInCr 4-x Cu x O8 ceramic sample at different frequencies, where the abscissa is the temperature and the ordinate is the relative dielectric constant.
[0045] Figure 8 For the LiInCr of the present invention 4-x Cu x Temperature-spectrum curve of the dielectric loss of the LiInCr 4-x Cu x O8 ceramic sample at different frequencies, where the abscissa is the temperature and the ordinate is the dielectric loss.
[0046] Figure 9 For the LiInCr of the present invention 4-x Cu x Frequency-spectrum curve of the dielectric constant of the LiInCr 4-x Cu x O8 ceramic sample at different frequencies, where the abscissa is the frequency and the ordinate is the relative dielectric constant.
[0047] Figure 10 For the LiInCr of the present invention 4-x Cu x Temperature-spectrum curve of the dielectric loss of the LiInCr 4-x Cu x O8 ceramic sample at different frequencies, where the abscissa is the frequency and the ordinate is the dielectric loss.
[0048] Figure 11 Complex impedance diagram of the LiInCr 4-x Cu x O8 compound and fitting activation energy diagram of the LiInCr 4-x Cu x O8 ceramic of the present invention at different temperatures, where (a)-(d) the abscissa is the real part of the impedance and the ordinate is the imaginary part of the impedance; (e)-(h) the abscissa is 1000 divided by the absolute temperature T and the ordinate is the logarithm of the total resistance lnR.
[0049] Figure 12 For the LiInCr of the present invention under different temperatures 4-x Cu x Schematic diagram of the dependence of the imaginary part of the impedance of the LiInCr 4-x Cu x O8 ceramic material on frequency, where the abscissa is the frequency and the ordinate is the imaginary part of the impedance.
[0050] Figure 13 For the LiInCr measured at different temperatures of the present invention 4-x Cu x Graph showing the relationship between AC conductivity and frequency, where the abscissa is frequency and the ordinate is AC conductance. Detailed implementation manners
[0051] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0052] Embodiment 1:
[0053] As Figures 1 - 13 shown, the present invention provides a preparation method of spinel ceramic materials, including the following steps:
[0054] 1. Take Li2CO3, In2O3, Cr2O3 and CuO powders with a mesh size of 200, and weigh the samples according to the molar ratio of 1:1:(4 - x):2x, where x = 0, 0.2, 0.4, 0.5.
[0055]
[0056] 2. Place the weighed powders in a corundum crucible and pre - sinter at 900 °C for 4 hours.
[0057] 3. Pour the pre - sintered powders into a grinding jar, add zirconia balls and absolute ethanol and ball - mill for 2 hours, where absolute ethanol is used as the ball - milling medium.
[0058] 4. Pour the ball - milled powders into a flat ceramic dish and dry in an electro - thermal blast drying oven at 85 °C for 4 hours for easy scraping.
[0059] 5. Put the scraped powder materials in an agate mortar, add 10% by mass of polyvinyl alcohol ceramic glue and mix with a grinding rod to make the glue and the powder evenly mixed.
[0060] 6. Sieve the powder materials added with glue through a 40 - mesh stainless - steel sieve.
[0061] 7. Press the sieved powder materials into a disc with a diameter of 13 mm and a thickness of 1 - 2 mm using a tablet press and place it in a corundum crucible.
[0062] 8. Place the corundum crucible containing the disc in a muffle furnace, calcine at 550 °C for 4 hours to remove the binder. Then directly raise the temperature to 1000 °C and calcine for 24 hours (the sintering temperature threshold is 1000 ± 20 °C, and the sintering time threshold is 24 ± 2 hours), and then the LiInCr 4-x Cu x O8 ceramic sample is made.
[0063] Example 2:
[0064] A dielectric property test method for spinel ceramic materials, comprising the following steps:
[0065] A1. Dielectric constant and loss test: Measure the dielectric constant and dielectric loss of the sample using an impedance analyzer in the frequency range of 20 Hz - 30 MHz, and the test temperature range is from room temperature to 350 °C;
[0066] A2. Threshold determination: Set the dielectric property threshold, dielectric constant ≥ 5000 (low frequency 20 Hz), dielectric constant ≥ 7 (high frequency 30 MHz), dielectric loss ≤ 0.02 (high frequency 30 MHz). If the sample meets the threshold, it is determined as a high-performance dielectric material.
[0067] Example 3:
[0068] The present invention also provides a spinel ceramic material, which is prepared by the preparation method of the above spinel ceramic material.
[0069] For the LiInCr 4-x Cu x O8 ceramic sample prepared by the technical solution of the present invention was tested, and the results are as follows:
[0070] As Figure 5 shown, for the X-ray diffraction pattern of the LiInCr 4-x Cu x O8 ceramic sample, it can be seen that the phase formation is relatively pure, and there is no any impurity phase for the matrix and the sample with x = 0.2. Only for the highly doped samples with x = 0.4 and x = 0.5, there is a small In2O3 impurity phase.
[0071] As Figure 6 shown, for the scanning electron microscope picture of the LiInCr 4-x Cu x O8 ceramic sample, the irregularly shaped particles have a particle size distribution, and the particle size is about 2 μm. Compared with the matrix material, the grain size of the doped sample is slightly reduced, which may be due to the fact that the radius of the Cu 2+ ion (r Cu2+ = 72 p.m.) is not much different from the radius of the Cr 3+ ion (r Cr3+ = 69 p.m.). The SEM image of the particles looks very dense, and the pores can be ignored. The introduction of Cu 2+ ions will lead to more grain boundaries, which will affect the electrical properties.
[0072] Figure 7 and Figure 8 respectively show LiInCr4-x Cu x Variations of the temperature-dependent dielectric constant (εr) and dielectric loss (tanδ) of CuO8 samples at different frequencies. For all samples, the dielectric constant increases with increasing temperature. Generally, dipole, electronic, ionic, and space charge polarizations all affect the dielectric response. In addition, dipole and space charge polarizations are the main reasons for the spinel chromite structure. As the temperature increases, more charge dipoles in the system can switch due to thermal activation, so the polarization effect becomes stronger, resulting in an increase in the dielectric constant. At relatively high temperatures, the dielectric constant exhibits strong frequency dependence, indicating significant relaxation behavior. The dielectric loss reflects the phase difference due to energy loss in the sample. At room temperature and high frequency, the dielectric loss is about 0.01. This means that these compounds have potential applications at room temperature. We also found that copper substitution for chromium increases the dielectric constant and reduces the loss, indicating an improvement in insulation performance and a weakening of energy loss. As the Cu doping amount increases, the dielectric constant increases while the dielectric loss decreases, indicating an improvement in dielectric properties.
[0073] Figure 9 and Figure 10 respectively show the frequency-dependent dielectric constant (εr) and dielectric loss (tanδ) of LiInCr 4-x Cu x O8 samples at different temperatures. It was observed that as the frequency increased from 20 Hz to 30 MHz, the dielectric constant and loss of all samples decreased. As the frequency increases, space charge polarization has less and less time to orient in the direction of the applied signal. Therefore, the dielectric constant decreases with increasing frequency, highlighting strong dielectric dispersion. The dielectric loss decreases with increasing frequency, indicating the presence of leakage conduction.
[0074] Copper substitution increases the dielectric constant and reduces the loss at room temperature, indicating that electrical insulation is promoted and energy loss is weakened. The increase in εr with increasing Cu content may be due to two factors. (1) Copper substitution leads to an increase in the degree of structural disorder in the structure. (2) The substitution of larger Cu 2+ cations may increase the off-center displacement of Cr 3+ cations on the CrO6 octahedron. The decrease in tanδ after doping should result from a reduction in leakage current due to increased insulation. These compounds should be able to meet the possible applications of microelectronic technology at room temperature.
[0075] From the above four figures, it can be seen that at room temperature of 30 degrees, the sample with x = 0 has the minimum dielectric loss tanδ = 0.00122 at a frequency of 1.57×10 7 Hz, and at the same time ε rThe sample with =5.66; x = 0.5 has the maximum dielectric constant ε at a low frequency of 20 Hz r = 5895.79, while tanδ = 3.34. Overall, the sample with x = 0.4 has a relatively large dielectric constant ε r = 7.09 and a relatively small dielectric loss tanδ = 0.016. Therefore, the four materials prepared by the present invention can be selectively applied to different electronic circuits according to their dielectric properties. In previous studies on LiInCr4O8 polycrystalline materials (100 Hz - 1 MHz), at room temperature, its dielectric constant has a maximum value at 100 Hz, ε r = 18.42, while tanδ = 0.21; its dielectric loss has a minimum value at 1 MHz, tanδ = 0.028, while ε r = 7.89. Since the ceramic materials prepared by the present invention have a larger dielectric constant and a smaller dielectric loss than previous polycrystalline samples, and better dielectric properties, they can be used to manufacture high-performance capacitors, dielectric resonators, filters and other devices to improve the efficiency and stability of circuits. It has good application value in modern electronic industry.
[0076] Such as Figure 11 shown, is the complex impedance diagram of LiInCr 4-x Cu x O8 compounds at different temperatures. LiInCr 4-x Cu x O8 ceramic fitting activation energy diagram. Figure 11 (a)-(d) show the complex impedance diagrams of LiInCr 4-x Cu x O8 compounds at different selected temperatures. The analysis of the Cole-Cole diagram can distinguish the various effects of grain, grain boundary and electrode effects on the relaxation process of ceramic materials. For the compounds with x = 0 and x = 0.5, there are two incomplete semi-circles, indicating that the conduction is due to grain effect and grain boundary effect. For the samples with x = 0.2 and 0.4, only a sunken semi-circle can be observed, indicating that the conduction is caused by grain effect. The non-perfect semi-circle indicates that the relaxation of ceramic LiInCr 4-x Cu x O8 is non-Debye type. Usually, in ceramics, factors such as grain orientation, stress-strain phenomenon and atomic defect distribution will also lead to deviation from the ideal Debye type behavior. The calculation of the activation energy shows that LiInCr 4- x Cu x O8 is between 0.37 - 0.62 eV. Doping reduces the activation energy of the material.
[0077] Figure 12 Shows LiInCr at different temperatures 4-x Cux Variation of the imaginary part of impedance (Z”) in O8 with frequency. It is worth noting that for samples with x = 0 and x = 0.5, there are two peak maxima, while for samples with x = 0.2 and x = 0.4, only one peak can be observed. For all compositions, the peak maximum shifts to higher frequencies with increasing temperature, indicating that the temperature-triggered relaxation process dominates in the ceramic samples. In the impedance spectrum, the grain effect occurs at high frequencies and the grain boundary effect occurs at low frequencies. As the Cu doping amount increases, the resistivity of the material first increases and then decreases, reaching the maximum in the sample with x = 0.4, indicating that the insulation performance is most significant at this time.
[0078] Figure 13 Shows LiInCr measured at different temperatures 4-x Cu x Graph of the relationship between the alternating current conductivity of O8 and frequency. It can be observed that for all frequencies, σ ac increases with increasing measurement temperature, which is similar to the direct current resistance observed through the Cole-Cole plot. The lower value of σ ac at low frequencies is caused by the hindrance effect of ion movement occurring at the grain boundaries. Its characteristic is the direct current conductivity generated due to the long-distance translational movement of electrons. The high-frequency dispersion region is due to the conductivity relaxation phenomenon caused by short-range ion transport.
[0079] In summary, the LiInCr 4-x Cu x O8 ceramic material prepared by the present invention has excellent insulation, corrosion resistance, high temperature resistance, high hardness, low density, radiation resistance, etc. It is more compact, easier to form, and more practical than polycrystalline materials. It is pre-fired at a constant temperature of 900 °C for 4 hours, and after adding glue, it is sintered at 1000 °C for 24 h to form a phase. Previous polycrystalline samples were sintered at 1050 - 1150 °C, and the constant temperature time was longer, mostly 48 h or even several days. By comparison, the ceramic material prepared by the present invention has a lower sintering temperature and a shorter sintering time, reducing the volatilization of the raw material lithium carbonate Li2CO3. At the same time, anhydrous alcohol is used instead of deionized water during the ball milling process, making the prepared material have a higher purity. It has better dielectric properties than previous polycrystalline samples. The ceramic dielectric material prepared by the technology of the present invention has a larger frequency range (20 Hz - 30 MHz) in the dielectric property test, has a larger dielectric constant and a smaller dielectric loss, and has better dielectric properties. It can be used to manufacture high-performance capacitors, dielectric resonators, filters and other devices, improving the efficiency and stability of the circuit. It has good application value in the modern electronic industry.
[0080] The foregoing has shown and described the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and the descriptions in the specification are only preferred examples of the present invention and are not used to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed. The scope of protection claimed by the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a spinel ceramic material, characterized in that, It includes the following steps: S1. Take Li2CO3, In2O3, Cr2O3 and CuO powders, and weigh the samples according to the molar ratio of 1:1:(4 - x):2x. S2. Put the weighed powders in a corundum crucible for pre - sintering; S3. Pour the pre - sintered powders into a grinding jar, add zirconia balls and absolute alcohol, and ball - mill for 2 hours; S4. Pour the ball - milled powders into a flat ceramic dish and put it into an electro - thermal blast drying oven for drying; S5. Put the scraped powder materials in an agate mortar, add 10% by mass of polyvinyl alcohol ceramic glue, and mix and grind with a grinding rod to make the glue and the powder evenly mixed; S6. Sieve the powder materials after adding the glue; S7. Press the sieved powder materials into round pieces with a tablet press and put them in a corundum crucible; S8. Place the corundum crucible containing the wafers in a muffle furnace, calcine at 550 °C for 4 hours to remove the binder, and then directly raise the temperature to 1000 °C and calcine for 24 hours to obtain the LiInCr 4-x Cu x O8 ceramic sample.
2. The preparation method of the spinel ceramic material according to claim 1, characterized in that, The mesh number of the Li2CO3, In2O3, Cr2O3 and CuO powders in step S1 is 200 mesh.
3. The preparation method of the spinel ceramic material according to claim 2, wherein, The value of x in step S1 is 0, 0.2, 0.4, 0.
5.
4. The preparation method of the spinel ceramic material according to claim 3, wherein, The conditions for pre - sintering in step S2 are: pre - sinter at 900 °C for 4 hours.
5. The preparation method of the spinel ceramic material according to claim 1, wherein, Absolute alcohol is used as the ball - milling medium in step S3.
6. The preparation method of the spinel ceramic material according to claim 1, wherein The conditions for drying in step S4 are: dry at a temperature of 85 °C for 4 hours.
7. The preparation method of the spinel ceramic material according to claim 1, characterized in that, The diameter of the round pieces in step S7 is 13 mm, and the thickness is 1 - 2 mm.
8. The preparation method of the spinel ceramic material according to claim 1, characterized in that, The sintering temperature threshold in step S8 is 1000 ± 20 °C, and the sintering time threshold is 24 ± 2 hours.
9. The method for testing the dielectric properties of the spinel ceramic material according to any one of claims 1-8, characterized in that, It includes the following steps: A1. Dielectric constant and loss test: Use an impedance analyzer to measure the dielectric constant and dielectric loss of the sample in the frequency range of 20 Hz - 30 MHz, and the test temperature range is from room temperature to 350 °C; A2. Threshold determination: Set the dielectric property thresholds, dielectric constant ≥ 5000, dielectric loss tangent ≥ 7, dielectric loss ≤ 0.
02. If the sample meets the thresholds, it is determined as a high - performance dielectric material.
10. A spinel ceramic material, characterized in that, The spinel ceramic material is prepared according to the preparation method of the spinel ceramic material described in any one of claims 1 - 8.